Determination of optimal modes for the production of micro range metal powders; Applied Engineering Letters; Vol. 7, iss. 1 - Kuznetsov M. A. Maksim Aleksandrovich; Ilyashchenko D. P. Dmitry Pavlovich; Lavrova E. V. Elena Vladimirovna; Solodsky S. A. Sergey Anatolievich; Podgornykh O. A. Oleg Anatolievich; Verkhoturova E. V. Elena Vladimirovna (2022, 2022)
Title screen